A review on the hydrothermal ageing behaviour of Y-TZP ceramics. Issue 17 (1st December 2018) - Ramesh, S.; Sara Lee, K.Y.; Tan, C.Y.
Abstract: The state of understanding on the devastating effects of hydrothermal ageing on the properties of yttria-tetragonal zirconia polycrystal (Y-TZP) when exposed to humid environment are reviewed. The prime factors governing the ageing-induced tetragonal to monoclinic phase transformation include the tetragonal grain size, sintering techniques particularly two-step sintering, microwave sintering and electric field assisted sintering, and yttria content are discussed. In addition, the beneficial effects of sintering additives or dopants in promoting sintering as well as suppressing the ageing-induced monoclinic formation are also deliberated. Selective dopants and co-dopants such as copper oxide, alumina, iron oxide and magnesium oxide were found to be beneficial in suppressing hydrothermal ageing in zirconia. Other important boundary conditions to be considered when evaluating the ageing behaviour of Y-TZP includes the ageing environment i.e. temperature, medium and applied pressure which were discovered to have an impact on the rate of phase transformation. Furthermore, the effects of ageing-induced monoclinic formation on the surface topography and mechanical properties of Y-TZP are reviewed. This review indicated that the ageing of Y-TZP can be rather intricate as there are many combinatory factors that needs to be tailored in order to develop an ageing-resistant zirconia without compromising on the transformation toughening effect and other properties.